The Role and Regulation of Heat Shock Proteins in the Antarctic Alga Chlamydomonas priscuii - Vakulenko, Galyna (Université d'Ottawa / University of Ottawa, 2022)
Chlamydomonas priscuii is a psychrophilic green alga found 17 m below the permanently ice-covered surface of the Antarctic Lake Bonney, where it experiences a myriad of extreme environmental conditions, including low temperature, low light, and high salinity. While this habitat is extreme, it is also very stable, and this alga rarely experiences changes in its environment. Heat shock proteins (HSPs) are a ubiquitous family of chaperone proteins that perform important housekeeping and stress-related roles. In most organisms, including the model green alga Chlamydomonas reinhardtii, HSP expression is induced during abiotic stress to regain protein homeostasis – a process regulated by heat shock transcription factors (HSFs). This work shows that C. priscuii constitutively accumulates high protein levels of HSPs in steady-state conditions but fails to induce additional HSP accumulation during heat and low temperature, high and low salt, high light, and with canavanine treatment. In this study, a single HSF was identified in the C. priscuii genome. Comparative sequence analysis revealed that most domains characteristic of a functional HSF are conserved, but the expression of a full length HSF1 transcript could not be detected in the cell. Furthermore, the promoters of many C. priscuii HSPs lack binding sites for HSF. This work has shown that C. priscuii has a diminished ability to regulate HSP expression under stressful conditions, which we hypothesize is a result of life in an extreme but very stable environment. This is the first demonstration of a loss of HSP accumulation in green algae, which carries implications on the ability of psychrophiles to survive in the face of climate change.
Keywords: Antarctica; green algae; climate change; heat shock protein; heat shock transcription factor; temperature stress